Uso de estrategias de zona grís en entornos urbanos. Uso de tácticas no convencionales en la lucha por el relato (Journal of the Spanish Institute for Strategic Studies, 2024)
This article tries to analyze the intersection between  gray area strategies and urban environments vulnerabilities against these strategies. We research the characteristics and, mainly, the proceses processes that relate with the conflict, with special attention to unconventional tactics and urban environments. The importance of public opinion in our society as a fundamental objective of these actions is also analyzed, as well as the potential threats in cyberspace. Finally, it is about giving possible answers and highlighting deficiencies in this matter.